Calcium-permeable AMPA receptors provide a common mechanism for LTP in glutamatergic synapses of distinct hippocampal interneuron types. - Szabo, A; Somogyi, J; Cauli, B; Lambolez, B; Somogyi, P; Lamsa, K (2012)
Glutamatergic synapses on some hippocampal GABAergic interneurons exhibit activity-induced long-term potentiation (LTP). Interneuron types within the CA1 area expressing mutually exclusive molecular markers differ in LTP responses. Potentiation that depends on calcium-permeable (CP) AMPA receptors has been characterized in oriens-lacunosum moleculare (O-LM) interneurons, which express parvalbumin and somatostatin (SM). However, it is unknown how widely CP-AMPAR-dependent plasticity is expressed among different GABAergic interneuron types. Here we examine synaptic plasticity in rat hippocampal O-LM cells and two other interneuron types expressing either nitric oxide synthase (NOS) or cholecystokinin (CCK), which are known to be physiologically and developmentally distinct. We report similar CP-AMPAR-dependent LTP in NOS-immunopositive ivy cells and SM-expressing O-LM cells to afferent fiber theta burst stimulation. The potentiation in both cell types is induced at postsynaptic membrane potentials below firing threshold, and induction is blocked by intense spiking simultaneously with afferent stimulation. The strong inward rectification and calcium permeability of AMPARs is explained by a low level of GluA2 subunit mRNA expression. LTP is not elicited in CCK-expressing Schaffer collateral-associated cells, which lack CP-AMPARs and express high levels of the GluA2 subunit. The results show that CP-AMPAR-mediated synaptic potentiation is common in hippocampal interneuron types and occurs in interneurons of both feedforward and feedback inhibitory pathways.